Fargo - Coen, Joel; Coen, Ethan; McDormand, Frances; Macy, William H., 1950-; Buscemi, Steve, 1958-; PolyGram Filmed Entertainment (Firm) (United States : Gramercy Pictures, 1996)
Jerry Lundegaard, a car sales executive in Minnesota who is deeply in debt, goes to Fargo to meet Carl Showalter and Gaear Grimsrud to arrange their kidnapping of his wife, Jean. He plans to extort a million dollars from his father-in-law, Wade Gustafson, and pay them $80,000. Showalter and Grimsrud kidnap her but are stopped by a police officer, whom the latter kills. Marge Gunderson, the police chief of Brainerd, Minnesota, follows the trail of the killers to Minneapolis-St. Paul. Gustafson insists on paying the kidnappers and Showalter kills him. He buries most of the money and returns to find that Grimsrud has murdered Jean. Grimsrud then kills Showalter. Gunderson discovers their hideout and arrests Grimsrud. Lundegaard is arrested.
Based on a true story.
Executive producers, Tim Bevan, Eric Fellner ; director of photography, Roger Deakins ; music by Carter Burwell ; film editor, Roderick Jaynes.
Frances McDormand (Marge Gunderson), William H. Macy (Jerry Lundegaard), Steve Buscemi (Carl Showalter), Harve Presnell (Wade Gustafson), Peter Stormare (Gaear Grimsrud).
Keywords: Debt -- Minnesota -- Drama; Kidnapping -- Minnesota -- Drama; Murder -- Minnesota -- Drama; Police chiefs -- Minnesota -- Drama; Policewomen -- Minnesota -- Drama; Police films and programs; Drama; Comedies; Features